Evaluation of Sampling Precision for Native and Nonnative Fish in the Gila River Basin, New Mexico - Zach Klein; Matt Zeigler (Hydrobiology)
Biologists commonly use standard sampling protocols to ensure that data are comparable spatiotemporally. Data also need to be precise to allow for statistically meaningful comparisons. However, the effort needed to precisely sample desert fishes is unclear. We used a resampling approach to evaluate the effort requirements needed to precisely sample fishes among six wadeable rivers in the Gila River basin, New Mexico. We evaluated the number of samples that are necessary to obtain relative density estimates that had 25% relative standard error 80% of the time. We also estimated the effort needed to precisely characterize species richness. Our results indicate that precisely sampling fish in the Gila River basin is difficult. Sonora Sucker Catostomus insignis, Desert Sucker C. clarkii, Longfin Dace Agosia chrysogaster, and Speckled Dace Rhinicthyes osculus were generally the only species that could be precisely sampled. Characterizing the native species assemblage in the Gila River basin required between two and seven reaches, whereas the entire species assemblage could only be characterized in 50% of the study systems. The challenge of precisely sampling fish in the Gila River basin suggests that alternative sampling methods may be required to characterize changes in density or species distribution in desert Southwest systems.